The Natural Gas Conundrum Transformation of the Central Asian Energy Security Complex after 1991 - Lídl, Václav (Karolinum Press, 2023)
The study examines energy security in the Central Asia region, with an emphasis on the natural gas sector. The research presented in the book attempts to answer the question of whether the various state actors in Central Asia are more inclined towards a strategic or market-oriented approach to energy policy formulation. Answering this research question aimed at better understanding the approach of individual state actors towards large infrastructure projects such as the construction of the Central Asia-China Gas Pipeline. Based on the theoretical literature, a model was constructed to assess the natural gas sector in terms of energy policy formulation by individual state actors. This model was then applied to three case studies of key state actors within the Central Asian regional energy security complex. These are the case studies of Russia, China, and Turkmenistan.